Lugares de memória e vestígios do cangaço em Mossoró-RN. - Fernandes, Júlio César Lima (2022)
This work brings to collective learning, sensitive issues in the context of valuing memory that encompasses the facts and events that are linked to the unsuccessful attempt to invade Lampion in the city of Mossoró - RN in 1927. When choosing this fact, we took into account the fascination that these stories produce in various age groups and social classes, as they deal with anxieties that are often present in the human condition. The binomial hero and bandit constitute a very favorable theme for fomenting the discussion about the existing violence between groups formed by those who dominate the official narrative and those who had their voices and memories suppressed. This leads us to analyze and investigate this relationship, which according to Rui Facó (1968) is one of the preferences of readers and visitors who are part of groups potentially benefiting from the Tourist Guide of memories of cangaço in Mossoró. Not to mention that, whatever visitors who arrive and who want to know the city, they will be able to have their hands on the structured form or through digital media, a support that will make the experience of visiting the sites or points of Cangaço in Mossoró, more comprehensive and didactic. Therefore, this research brought up a problem which was: Does the city of Mossoró have the potential to offer its population and its visitors a tourist itinerary with traces of cangaço? By reflecting on this theme, we managed to reach the answers at the end of the proposed schedule that answer the reason for this gap in the city and, at the same time, we were able to make the cangaço tourist itinerary available in the city. By bringing people from the simple "people" to the center of the discussion of this theme, a historical repair is made, in many moments, counterpointing what was and is evidenced by the political authorities and press of the time, presented in newspapers, and public notes of the time.